2005
DOI: 10.1200/jco.2005.06.104
|View full text |Cite
|
Sign up to set email alerts
|

Unequivocal Delineation of Clinicogenetic Subgroups and Development of a New Model for Improved Outcome Prediction in Neuroblastoma

Abstract: We propose a new regression model for improved patient outcome prediction, incorporating tumor stage, chromosome 17, and amplification/deletion status. These findings may prove highly valuable with respect to more reliable risk assessment, evaluation of clinical results, and optimization of current treatment protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
155
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 162 publications
(176 citation statements)
references
References 39 publications
17
155
0
4
Order By: Relevance
“…However, the analysis of type 2b profiles shows that 1p and 11q deletions are not exclusive. On the other hand, previous studies have shown that localised tumours or those occurring in infants o1 year of age have numerical rather than structural abnormalities (Bilke et al, 2005;Vandesompele et al, 2005). In our series, a type 1 genomic profile is also associated with an age o1 year at diagnosis and with localised disease.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…However, the analysis of type 2b profiles shows that 1p and 11q deletions are not exclusive. On the other hand, previous studies have shown that localised tumours or those occurring in infants o1 year of age have numerical rather than structural abnormalities (Bilke et al, 2005;Vandesompele et al, 2005). In our series, a type 1 genomic profile is also associated with an age o1 year at diagnosis and with localised disease.…”
Section: Discussionsupporting
confidence: 44%
“…A more recent study based on the pooled CGH data of 231 samples from several institutions has confirmed this classification (Vandesompele et al, 2005). Variations in the copy number of whole chromosomes was more frequently observed in localised disease, of favourable histology, and in infants, with recognition of a survivor signature conferring 100% 5-year survival in stage 1, 2 or 4s tumours presenting with whole chromosome 17 gain, whereas structural aberration patterns were a significant predictor of poorer outcome.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Loss of chromosome 1p material, occurring predominately through an unbalanced t(1;17) that also results in gain of 17q (Van Roy et al, 1994), is a common chromosomal imbalance found in NB and occurs preferentially in tumors with MYCN amplification (MNA) (Fong et al, 1989). All three of these nonrandom genetic abnormalities, loss of 1p, gain of 17q and MNA, are independently associated with a poor clinical outcome (Brodeur et al, 1984;Spitz et al, 2003;Attiyeh et al, 2005;Vandesompele et al, 2005).…”
mentioning
confidence: 99%